Benchmarking the Efficiency of Public Expenditure in the Russian Federation - Hauner, David (IMF Working Papers; Working Paper, 2007)
This paper benchmarks the efficiency of public expenditure in the social sectors in the Russian Federation relative to other countries and among the country's regions. It finds that there is substantial room for efficiency gains, particularly in health care and social protection, although less so in education. An econometric analysis of efficiency differences between the regions suggests that they are positively related to per capita income and the quality of governance and democratic control, while they are negatively related to the share of federal transfers in the respective region's government revenue and the level of spending relative to gross regional product.